Robust Aspergillus terreus biofilm supported on graphene oxide/hematite-nanocomposites for adsorption of anthraquinone dye. Issue 51 (1st November 2016) - Mawad, Asmaa M.M.; Yousef, Naeima M.H.; Shoreit, Ahmed A.M.
Abstract: Hematite/graphene oxide (FGO) nanocomposites were used as a supporting surface for the fungus Aspergillus terreus AUMC-050 to form AFGO biofilm. Different techniques were used for characterization of nanocomposites and biofilm such as IR, Fourier transform infrared, Scanning electron microscopy, Transmittance Electron Microscopic, Brunauer–Emmett–Teller surface area, and Raman Spectroscopy. The effect of initial dye concentration (0–300 mg/L), contact time (0–80 min), pH values (2.0–8.0), and temperature (10–50°C) was studied. The maximum adsorption capacity of dye using AFGO biofilm was 160 mg dye/g at pH 2.0, and the contact time was 50 min. The best fitted equilibrium and kinetic model were found to be Langmuir and pseudo-first order, respectively. Various thermodynamic parameters were evaluated to determine the nature of biosorption process. The negative value of Δ G and Δ H ° indicated spontaneity and exothermic behavior of the adsorption process. Using of microbial biofilm supported on nanocomposite material is a new approach for adsorption of dyes from water body.